2013
DOI: 10.3109/00498254.2013.823529
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the role of P-glycoprotein inin vitrodrug permeability studies with the bovine brain microvessel endothelial cells

Abstract: 1.  Currently available in vitro blood-brain barrier models all have recognized restrictions. In addition to leakiness, inconsistent data about P-glycoprotein mediated efflux limit the attractiveness of the primary bovine brain microvessel endothelial cells (BBMECs). Therefore, we re-evaluated the role of P-glycoprotein mediated efflux with two culture conditions in BBMECs for prediction of drug permeability of potential P-glycoprotein substrates. 2.  BBMECs were monocultured on filters on petri dishes and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…A recent study by Hakkarainen et al demonstrated P-gp expression in primary bovine endothelial cells with western blotting and immunofluorescence, as well as P-gp function as evaluated by the calcein-AM assay, but did not observe a net transendothelial P-gp-mediated efflux. The authors also reported low TEER values and high sucrose permeabilities, indicating that the paracellular flux component may have masked the transcellular efflux [20]. We found high TEER values in this study, although they decreased gradually during the transport experiments.…”
Section: Polarized Transport Of Efflux Transporter Substrates May Be contrasting
confidence: 48%
See 2 more Smart Citations
“…A recent study by Hakkarainen et al demonstrated P-gp expression in primary bovine endothelial cells with western blotting and immunofluorescence, as well as P-gp function as evaluated by the calcein-AM assay, but did not observe a net transendothelial P-gp-mediated efflux. The authors also reported low TEER values and high sucrose permeabilities, indicating that the paracellular flux component may have masked the transcellular efflux [20]. We found high TEER values in this study, although they decreased gradually during the transport experiments.…”
Section: Polarized Transport Of Efflux Transporter Substrates May Be contrasting
confidence: 48%
“…Immunocytochemical stainings further confirmed the presence of P-gp, Bcrp and Mrp-1 in the endothelial cells as well as in freshly isolated capillaries. P-gp and Bcrp expression have previously been shown in BBB models [6,19,20,30], whereas Mrp expression is more controversial. Mrp-1 has been shown on the mRNA level in bovine brain capillaries [9] and in bovine and porcine brain endothelial cells [9,68] and on the protein level in rat brain endothelial cells [30], but also Mrp-4 and -5 mRNA have been shown in bovine and porcine endothelial cells [9,10,68].…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 99%
See 1 more Smart Citation
“…Since the expression of P-glycoprotein alone cannot positively determine the functionality of the P-gp efflux pump, a quantitative approach using bidirectional permeability was used, instead of methods that only evaluate the level of expression of proteins such as a Western blot or qPCR, to evaluate its functional expression. We measured the apical-to-basolateral (AB) and basoalteral-to-apical (BA) permeability of [ 3 H]-dexamethasone, which is a substrate for the P-gp efflux pump across b.End3 cell monolayers in the bi- and triculture models.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, many reports have shown bovine BBB models with TEER values in the range of 30-150 cm 2 and/or lack of functional activity of both ABC and SLC-transporters known to be present at the BBB in vivo. 149,166,173,198,199 Intra-laboratory variations are evident in a series of publications by the group of de Boer where TEER varies from high values around 800 cm 2 to around 150-300 cm 2,19,187,192,193 using the same model in the same laboratory. This is even clearer in a study by Helms et al, 53 where TEER averages varied from 327 AE 30 cm 2 to 2555 AE399 cm 2 across model batches within the same study.…”
Section: Mouse Models -Immortalized and Primary Mouse Brain Endothelimentioning
confidence: 98%